2023
DOI: 10.3390/socsci12020068
|View full text |Cite
|
Sign up to set email alerts
|

Looking at Resilience among Transgender and Gender Diverse People in Portugal: Gender Affirmation Paths and Parenting Aspirations

Abstract: The transgender and gender diverse (TGGD) population is highly diverse. To date, research on the association of the various family–parenthood aspirations of TGGD people with distinct affirming paths and identities remains scarce. A survey was conducted aiming to characterize the TGGD population’s diversity and socio-demographic profile. A community-based convenience sample of 115 self-identified TGGD adults living in Portugal was collected. Most of the participants (69%) did not have any children, 10% had chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…Alain Giami, Emmanuelle Beaubatie, and Jonas Le Bail collaborated with transgender organizations and healthcare experts in France to create a survey questionnaire [55,56]; this questionnaire featured one open-ended question designed to capture gender identities among the participants by asking the respondents to describe their current gender identification using their own phrasing. The same protocol was developed in Brazil [57], Italy [58], Chile [59], and Portugal [60].…”
Section: Methodsmentioning
confidence: 99%
“…Alain Giami, Emmanuelle Beaubatie, and Jonas Le Bail collaborated with transgender organizations and healthcare experts in France to create a survey questionnaire [55,56]; this questionnaire featured one open-ended question designed to capture gender identities among the participants by asking the respondents to describe their current gender identification using their own phrasing. The same protocol was developed in Brazil [57], Italy [58], Chile [59], and Portugal [60].…”
Section: Methodsmentioning
confidence: 99%
“…The challenges listed were: discrimination and prejudice, exhaustive concern with protecting children from possible attacks [16][17][18][19][20] , difficulty in aligning gender performance and normative notions of paternity 6,21 , need for legal support 22 , absence of family emotional support and impaired mental health 19,23 . Another study also revealed vulnerability to depression and anxiety 24 due to stigma and violence.…”
Section: Introductionmentioning
confidence: 95%
“…Os desafios elencados foram: discriminação e preconceito, preocupação exaustiva em proteger os/as filhos/as de possíveis ataques [16][17][18][19][20] , dificuldade de alinhamento entre performance de gênero e as noções normativas de paternidade 6,21 , necessidade de apoio jurídico 22 , ausência de suporte emocional familiar e comprometimento da saúde mental 19,23 . Outro estudo ainda revelou a vulnerabilidade à depressão e ansiedade 24 , em função do estigma e violência.…”
Section: Introductionunclassified